The role of discovery learning in efforts to develop students' critical thinking abilities - Manurung, Alberth Supriyanto; Pappachan, Princy (Intelektual Pustaka Media Utama, 2025)
This research aims to determine the role of developing and implementing discovery learning models to develop students' critical thinking skills in mathematical story problems. The search was carried out in the even semester of 2022/2023 with research subjects totaling 30 fourth semester elementary school education students. The research was conducted using qualitative analysis methods with data collection through observation, interviews, and documentation. The discovery learning model is implemented through learning stages, namely training students to use various concepts, principles, and skills they have learned to solve the mathematical story problems they face. The research results show that the discovery learning model has an impact on the development of critical thinking skills because the research's observations of critical thinking abilities result in the capacity to recognize, evaluate, and resolve narrative difficulties as well as to reason rationally and ethically to conclude. The discovery learning model provides students with the opportunity to apply learning based on solving mathematical story problems, allowing students to develop critical thinking skills.